Grammar Connection 3 : Structure Through Content - Carlisi, Karen (Australia Heinle Cengage Learning, 2008)
Offers a basal program in Academic, Adult, and International programs. This title develops the skills that are useful for students planning to enroll in college-level courses, adults planning to return to college, or high school students in preparation for college
Include Color Illustration and Index
Keywords: English language--Grammar -- English language